Strategies in simultaneous interpreting: A review - Trisnawati, Ika Kana; Netta, Ayuna (Accentia: Journal of English Language and Education, 2020)
Simultaneous interpreting is an interpreting mode which occurs simultaneously between the interpreter and the speaker. This paper discusses simultaneous interpreting and the strategies used in simultaneous interpreting. Simultaneous interpreting gives more challenges for the interpreter since the interpreter has to translate orally what has been said within the time allowed by the speed of the speaker. Thus, it is more complicated and needs more attention to the output and active language skills.